Register perawatan kulit (soins de la peau) bahasa Prancis pada situs Aufeminin - Rahayu, Widya Arumdwita; Ratna; Ekowati, Sri Harini (Franconesia, 2022)
Language cannot be separated from the context which it is used. Diversity in society are reflected in language. For example, it may influence the amount of variety of language use by one people in daily basis. One of the language varieties that commonly used in a specific field or domain called register. This study aims to identify the linguistic for and the meanings of the French registers of skincare. The object in this study is the register of skincare used in article on the Aufeminin website.